BIOSTIMULATION OF INDIGENOUS BACTERIA FROM BENTAYAN 38 OIL RESERVOIR TO ENHANCED OIL RECOVERY - Lestari, Sari
Microbial Enhanced Oil Recovery (MEOR) is one of the technologies that utilize microbes to increase oil recovery. The approach that has been widely used MEOR is biostimulation. In this research, the stimulation of the growth of indigenous bacteria that includes the type of nutrition and the differences of feeding on a laboratory scale. This study was aiming at getting the right combination ofthe nutrient and the feeding time in improving the quality of the physical characteristics of oil and the production of some bacterial metabolites. Based on the results of the previous study (Khendarsyah, 2015), three types of nutrientswas chosen, namely nutrition 12 (Molasses 5% + 0.5% + NPK DAP 0.25%), nutrition 15 (Molasses DAP 5% + 0.25% + 0.25% NPK) and nutrition 28 (NPK Molasses 8% + 0.24%). The feeding time was divided into 3 types, which were every 7 days, 14 days and 21 days. The analysis was conducted consisting of the growth of facultative and anaerobic bacteria and also the physical characteristic of oil that was comprised of IFT (interfacial tension) and viscosity, GC-MS (Gas Chromatography-Mas Spectrometry), and bacterial communities analysis using the SSCP techniques (single-strand conformation polymerphism). The combination treatment between the nutrition composition and the feeding times showed the progressive result of the growth of indigenous bacteria and the production of bacterial metabolites such as gas and crude surfactant. The best growth of facultative and anaerobic bacteria were generated by the treatment of 15*7 waslog 6,25 CFU/mL total of facultative cell and of 12*7 was log 5,09CFU/mL of anaerobic total cell. The treatment of nutrition 28 and feeding every 21 days resulted the best decrease of viscosity dan IFT value, which wereabout 6.63 cP and 8.1 dyne / cm, respectively GC-MS analysis showed the varying results in the concentration of hydrocarbons, aliphatic and aromatic fractions. The alteration in the community at the end of the incubation period showed the highest diversity of bacteria obtained at treatment nutrition 28 feeding 21 days.